Strength and behaviour of reinforced geopolymer concrete short columns - Sujatha; Kannapiran; Nagan, K. (Journal of Structural Engineering, 2024)
Most of the published works on Geopolymer to date were related to the study of properties of Geopolymer paste, mortar or concrete, evaluated from small sized specimens without reinforcements. In addition, only limited, countable works on structural elements such as beams and columns have been reported. In this experimental work, Fly ash, a vital by-product released from thermal power stations is utilized as a feedstock for inorganic polymer binders. An attempt has been made to study the load-deflection behaviour and compressive strength of reinforced Geopolymer concrete short columns of M30 and M50 grade concrete, under axial compression. Totally, 12 specimens of M30 and M50 grade short columns were fabricated. Six specimens each for low calcium fly ash based reinforced Geopolymer concrete as well as ordinary Portland cement reinforced concrete. The columns were 125mm x 125mm in cross-section with overall length of 1000mm. The longitudinal reinforcement ratio was kept constant throughout the study as 2.89%. The load carrying capacity and deflection pattern were arrived and compared with Ordinary Portland cement reinforced concrete specimens.